Leucopholiota decorosa: a newly recorded species of Tricholomataceae (Agaricaceae) in China - WANG Shurong; YUAN Yuan; LIU Yang; MENG Junlong (浙江大学学报. 农业与生命科学版, 2020)
One species of Leucopholiota was collected from Pangquangou National Nature Reserve in Jiaocheng County, Lüliang City of Shanxi Province during the investigation on species diversity of Tricholomataceae from 2017 to 2018, and it was identified by morphological and molecular methods. The morphological, growing habitat and ecological characteristics were recorded by fresh specimens in the field and the microscopical characters were examined and measured in detail under an optical microscope and a scanning electron microscope. Its main characters were as follows: the surface of pileus was dry with 3.0-5.5 cm in diameter, and covered with numerous, introvert and rusty-brown scales; the lamella was white, crowed, serrated on the edge, slightly depressed at the border with stipes, which was 2.5-5.1 cm long and 0.5-1.0 cm in diameter, and covered with rusty-brown scales as that on the surface of pileus from the bottom of stipes to the rings and with smooth stipes on the upper part of rings; spores were (4.11-5.95) μm×(3.19-4.09) μm, amyloid, hyaline, and oblong; basidia was (15.38-20.89) μm×(5.21-6.08) μm; cheilocystidia was (14.70-21.30) μm×(3.52-5.38) μm, nearly clavate or fusiform, hyaline, with a pointed bump at the top. The internal transcribed spacer (ITS) district of rDNA extracted from this species was specifically amplified and a fragment with 651 bp was acquired. The amplified sequence was similarity with Leucopholiota decorosa at a level of 99.2%. With combinations of morphology, molecular identification and phylogenetic analysis, the species collected on the rotten wood of Betula platyphylla Suk. was identified as L. decorosa, which is the first recorded species of Leucopholiota in China. It provides a basis for the research on the genus Leucopholiota in China.